Mechanical performance of laser powder bed fused Ti-6Al-4V: The influence of filter condition and part location - Mohammad Salman Yasin; Kevin Stonaker; Shuai Shao; Nima Shamsaei (Additive Manufacturing Letters)
Deteriorated filter condition in laser powder bed fusion (L-PBF) systems may negatively impact shield gas flow, causing inadequate spatter particle/plume removal, leading to laser beam attenuation and reduction in melt pool depth, and potentially causing more frequent formation of volumetric defects. This work investigated the effects of filter condition and part location on the micro-/defect-structure and mechanical behavior, including tensile and fatigue, of Ti-6Al-4V parts fabricated by L-PBF. Interestingly, within the manufacturer recommended service intervals, no specific effect of filter condition could be observed on the micro-/defect-structure or the mechanical behavior of the fabricated parts. However, the parts’ defect-structures were affected by their location, with ones located near the center of the build plate having less porosity than the ones located away. Although these defects did not affect the tensile properties, they frequently observed to initiate fatigue cracks (the critical defects sizes were often in the range of a few tens of micrometers). Therefore, their sensitivity to location resulted in the location dependence of the fatigue behavior.